Mechanism and kinetics of peptide partitioning into membranes from all-atom simulations of thermostable peptides - Ulmschneider, Martin B.; Doux, Jacques P. F.; Killian, J. Antoinette; Smith, Jeremy C.; Ulmschneider, Jakob P. (Journal of the American Chemical Society, 2010)
Partitioning properties of transmembrane (TM) polypeptide segments directly determine membrane protein folding, stability, and function, and their understanding is vital for rational design of membrane active peptides. However, direct determination of water-to-bilayer transfer of TM peptides has proved difficult. Experimentally, sufficiently hydrophobic peptides tend to aggregate, while atomistic computer simulations at physiological temperatures cannot yet reach the long time scales required to capture partitioning. Elevating temperatures to accelerate the dynamics has been avoided, as this was thought to lead to rapid denaturing. However, we show here that model TM peptides (WALP) are exceptionally thermostable. Circular dichroism experiments reveal that the peptides remain inserted into the lipid bilayer and are fully helical, even at 90 °C. At these temperatures, sampling is ∼50−500 times faster, sufficient to directly simulate spontaneous partitioning at atomic resolution. A folded insertion pathway is observed, consistent with three-stage partitioning theory. Elevated temperature simulation ensembles further allow the direct calculation of the insertion kinetics, which is found to be first-order for all systems. Insertion barriers are ΔHin⧧ = 15 kcal/mol for a general hydrophobic peptide and ∼23 kcal/mol for the tryptophan-flanked WALP peptides. The corresponding insertion times at room temperature range from 8.5 μs to 163 ms. High-temperature simulations of experimentally validated thermostable systems suggest a new avenue for systematic exploration of peptide partitioning properties.
Gesehen am 26.01.2024